شعرية الحذف والإطناب عند أدونيس ( مهيار الدمشقي أنموذجا ) - Al-Azzam, بديع أحمد حسن (Jadara Journal of Social Sciences, 2025)
This paper theoretically handles the idea of omission and redundancy with a practical application in a modern poetic text for, Adonees, the Syrian well-known creative writer. This poet enjoys a unique creative feature, and he holds an elevated poetic experience that is influential in the modern Arabic poetry experiment. How thus has his poetic sense become dominant through omission and redundancy especially that the normal language with its strict rules might fail to express what the poet wants to say?. It would be necessary though to violate these well-established rules, destroy the traditional standards, and create a poetic language that gains its value of beauty by deviating the language from what is normal; the poetics is thus an organized violence that is practiced against the normal speech.